2014
DOI: 10.11114/ijsss.v3i1.519
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors of Men for Mental Health and the Impact of Diverse Cultural Backgrounds

Abstract: A growing research body suggests that men are less likely than women to seek help from professional counselors for mental health problems and stressful life events (Komiya, Good, & Sherrod, 2000). Untreated mental health problems can have a significant impact on the health and development of the client as well as the client's family members. Various factors such as help-seeking attitudes influence men's help-seeking behaviors in regard to mental health services. Males demonstrate less positive attitudes toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
2
16
0
2
Order By: Relevance
“…Furthermore, the finding that women's partners struggle to identify their own needs and seek help also corresponds with previous research that notes how traditional masculine role models and norms emphasize self‐reliance and emotional control (Addis & Mahalik, ), making it more difficult for men to ask for help (Lindinger‐Sternart, ).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the finding that women's partners struggle to identify their own needs and seek help also corresponds with previous research that notes how traditional masculine role models and norms emphasize self‐reliance and emotional control (Addis & Mahalik, ), making it more difficult for men to ask for help (Lindinger‐Sternart, ).…”
Section: Discussionsupporting
confidence: 84%
“…However, not all people seek help when problems occur. For example, research indicates that men were less likely than women to seek help from mental health professionals for a variety of reasons [ 12 , 13 ]. When psychological problems occur, males demonstrate less positive attitudes toward seeking help in order to avoid talking about stressful events and painful feelings because of masculine norms and stigma [ 13 ].…”
Section: Introduction Background and Settingmentioning
confidence: 99%
“…Most differences in seeking help were based along gender lines due to emphasis on masculinity and femininity inclinations and cultural attitudes to mental health. Previous research found that males were the most resistant to seeking help (Komiya et al, 2000;Lindinger-Sternart, 2014). In addition, males who were engaged in sports or armed forces occupations identified themselves to a higher level with the norms of masculinity and toughness, and often failed to recognize the benefits of seeking professional help from mental health specialists such as counselors, psychologists, and psychiatrists (Mundia, Shahrill et al, 2016;Steinfeldt & Steinfeldt, 2012).…”
Section: Research On Coping and Help Seeking In Brunei Educational Comentioning
confidence: 99%